The Effect of free weight exercises to develop the maximum Oxygen power (phosphagen) for the young footballer, ages (15) years old. - Sadon, Saad (Journal of Physical Education, 2018)
The introduction of the research lies on the importance of the training program should be include exercises in free weight to develop physical & physiological components and this was the problem of the research. The research recommends in the final the using of the free weight exercises include coaches programs for the whole footballer in sport club and in the special Amoo Baba Football school, for the age (13,14,16) years old.